EDUKASI ZERO WASTE LIFESYLE MELALUI MEDIA SOSIAL TERHADAP SISWA GENERASI Z DI SDN CIPUTAT - Siti Sopiaturida; Anna Maria Oktaviani; Rifa'i (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the effectiveness of zero waste lifestyle education through social media on increasing knowledge, pro-environmental attitudes, and zero waste behavior adoption among Generation Z in elementary schools. The growing waste problem, especially in Indonesia, demands innovative solutions, and Generation Z, as digital natives, are identified as potential agents of change. The continuously increasing waste problem in Indonesia has severe impacts on the environment, health, and economy, exacerbated by suboptimal waste management practices and increasing waste generation due to urbanization and consumerism. This study aims to evaluate the effectiveness of zero waste lifestyle education via social media in enhancing knowledge, attitudes, and zero waste behavior among Generation Z students at SDN Ciputat.